Analysis on performance and emission characteristics of corn oil methyl ester blended with diesel and cerium oxide nanoparticle - Muruganantham P; Pandiyan P; Ravishankar Sathyamurthy (Case Studies in Thermal Engineering, 2021)
There are other issues related to humans, including respiratory problems and even death. The present study deals with the analysis of cerium oxide nanoparticles at different concentration in corn oil methyl ester diesel blend with an optimum concentration of biodiesel of 10% with diesel fuel. The concentration of CeO2 nanoparticles with the COB10 is varied in the range of 25, 50, and 75 ppm. Results showed that the physicochemical properties of the fuel improved with the addition of CeO2 nanoparticles. The brake thermal efficiency (BTE) of the engine is improved with an optimum concentration of 50 ppm CeO2 nanoparticle with the fuel, and it is found as 34.7% whereas, the formation of NOx is increased. The other emission from the engine, such as CO, UBHC decreased with increased oxygen content available in the fuel with nano additives. At maximum engine load, the UBHC is reduced by 11, 16.6, and 20.8% for COB10, COB10 + 25 ppm, COB10 + 50 ppm respectively. Also, the reduced ignition delay reduced the formation of CO and unburnt hydrocarbons. From the experimental study it is found that the optimized nanoparticle concentration with COB10 is 50 ppm, which costs around Rs. 8. Similarly, the total cost of biodiesel with cerium oxide nanoparticles is estimated as Rs. 76/kg.